An integrated lean methodology for improving patient flow in an emergency department – case study of a Saudi Arabian hospital. Issue 13 (3rd October 2018) - Al Owad, Ali; Samaranayake, Premaratne; Karim, Azharul; Ahsan, Kazi Badrul
Abstract: This study presents an integrated lean methodology for improving patient flow by identifying root causes of patient flow problems and proposing a lean patient flow process in emergency departments (EDs). The methodology combines the 'voice of process', the 'voice of customers' and the 'voice of staff' to identify non-value-added activities in the ED process. This integration was used to model, evaluate and improve work and process flow in the hospital's ED. The current activities were analysed using process mapping and the A3 problem-solving sheet as visual tools to identify sources of waste. Aseer Central Hospital in Saudi Arabia was selected as the organisational case for this research. The study identified several critical areas of waste that significantly affect patient flow in the ED. The investigation reveals that these wastes were mainly related to the quality management, ED facilities, patients, physicians, nurses, administration, data/information and uncertainty/changes to work schedules in treatment. Based on the identified wastes, recommendations are made to design a lean process flow by eliminating root causes of overcrowding and waste in EDs. The proposed process model links key areas associated with the root causes of patient flow problem and highlighting critical areas that need improvement.